AI-POWERED HEALTHCARE REVOLUTION: AN EXTENSIVE EXAMINATION OF INNOVATIVE METHODS IN CANCER TREATMENT - Murad Khan; Ashish Shiwlani; Muhammad Umer Qayyum; Abdul Mannan Khan Sherani; Hafiz Khawar Hussain (CV. Multi Kreasi Media, 2024)
Abstract: This study examines the various ways that artificial intelligence (AI) is being used into the field of cancer medicine, with an emphasis on innovative techniques and advances in healthcare. The article, titled